Hippocampal Neurochemical Pathology in Patients with Panic Disorder - Atmaca, Murad; Yildirim, Hanefi; Gurok, M. Gurkan; Akyol, Muammer; Koseoglu, Filiz (Korean Neuropsychiatric Assoc, 2012)
Objective In the present study, we measured hippocampal N-acetyl-l-aspartate (NAA), choline (CHO) and creatine (CRE) values in patients with panic disorder and healthy control subjects using in vivo H-1 MRS. Methods We scanned 20 patients meeting Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) criteria for panic disorder and 20 matched healthy controls with a 1.5 Testa GE Signa Imaging System and measured of NAA, CHO, and CRE in hippocampal regions. Results When NAA, CHO and CRE values were compared between groups, statistically significant lower levels for all ones were detected for both sides. Conclusion Consequently, in the present study we found that NAA, CHO and CRE values of the patients with panic disorder were lower than those healthy controls. Future studies involving a large number of panic patients may shed further light on the generalizability of the current findings to persons with panic disorder. Psychiatry Investig 2012;9:161-165
Keywords: N-acetylaspartate; Creatine; Choline; Panic disorder; H-1 MRS